Network pharmacology and multi-omics validation of the Jianpi-Yishen formula in the treatment of chronic kidney disease - Li, Yuyan; Luo, Yueming; Hu, Yilan; Li, Siting; Li, Guandong; Zhang, Wanyangchuan; Gu, Xiufen; Wang, Jianting; Li, Shunmin; Cheng, Hong (Frontiers in Immunology, 2025)
ObjectiveChronic kidney disease (CKD) is a major global health problem. In clinical practice, the Chinese patent herbal medicine Jianpi-Yishen (JPYS) formula is commonly used to treat CKD. However, the molecular mechanisms by which JPYS targets and modulates the host immune response remain unclear.MethodsThis study utilized network pharmacology, RNA sequencing (RNA-seq), and metabolic analyses using in vivo and in vitro models to investigate the impact of the JPYS formula on inflammation and the immune system. Specifically, the study focused on macrophage polarization and metabolic changes that may slow down the progression of CKD.ResultsA total of 14,946 CKD-related targets were identified from the GeneCards and Online Mendelian Inheritance in Man (OMIM) databases through network pharmacology analyses. 227 potential targets of the JPYS formula were predicted using the TCMSP database. Additionally, network diagram demonstrated that 11 targets were associated with macrophage activity. In vivo studies indicated that the JPYS formula could reduce blood urea nitrogen and serum creatinine in adenine-induced CKD rats. Furthermore, the formula inhibited inflammatory damage and abnormal macrophage infiltration in this CKD model. RNA-seq, proteomic and metabolic analyses identified the regulation of amino acid metabolism by betaine, specifically referring to glycine, serine, and threonine metabolism, as a key target of the JPYS formula in slowing the progression of CKD. In addition, in vitro studies suggested that JPYS may enhance tryptophan metabolism in M1 macrophage polarization and betaine metabolism in M2 macrophage polarization.ConclusionsThe JPYS formula has been shown to have beneficial impact on CKD; a key mechanism is the mitigation of inflammatory damage through the interaction between amino acid metabolism and macrophage polarization. Of specific importance in this context are the roles of tryptophan in M1 polarization and betaine in M2 polarization.